Unintended Consequences of Special Education and Consideration of Change - Juli L. Taylor, MA; William A. Proffitt, PhD
This scholarly review presents a case for transforming special education rather than reauthorizing special education law in its present form and, in doing so, reconceptualizing the inclusion movement to recognize marginalizing influences. A comprehensive review of research, policy reviews, and observations of praxis is undertaken to examine current U.S. special education law. Three unintended consequences are identified: (a) the least restrictive environment provision; (b) incremental successes of the inclusion movement$1 (Bs emphasis on placement; and (c) the effort to promote racial integration in current special education policy. While unintended consequences cannot be foreseen, the structure of the Individuals with Disabilities Education Act (IDEA) has changed little since the 1970s despite evolving praxis and understandings of social justice. This article is intended to facilitate a conversation about a path forward for special education, including whether IDEIA should be reauthorized in its present form, or what form might be taken under alternative policy.s